Fintech Development, RegTech and Financial Institutions in Ghana: Starting with The Regulatory Sandbox (International Journal of Business Innovation, 2023)
This paper examines the development of Fintech in Ghana, focusing on policy, legal, and technical aspects. It analyzes Ghana's regulatory sandbox and Fintech laws, including consumer protection, data protection, and cyber security. The study explores the evolution of regulations and their impact on the Fintech landscape, as well as the use of technology by financial regulators and Fintech companies for supervision and compliance. Assessing challenges and industry stability, the paper evaluates the potential of Regtech to transform Ghana's financial regulatory model. Policy recommendations are provided to enhance the financial Regtech framework. Employing a multimodal approach, this study provides a comprehensive analysis of Fintech in Ghana, highlighting the importance of a coordinated approach to Fintech policy development and implementation
Keywords: Fintech Development; Financial Regulations; Regtech; Inclusive Finance